A study of the prevalence of anxiety symptoms in school children and their association with parenting style - Singh, Smita; Rath, T. K.; Mahajan, Saurabh; Pandit, Prashant; Mehrotra, Sameer (International Journal Of Community Medicine And Public Health, 2025)
Background: Anxiety disorders very often precede the onset of other psychiatric disorders. A continuum of factors including conflict or violence in the family, damaging life events or a low sense of connect with the environment can risk mental health causing an indelible effect on a growing adolescent. Parental behaviour may be the strongest and the earliest source of molding of habits and internalization for the children. Also, there is greater reluctance in seeking professional mental health for adolescents and especially so for girls. Methods: A cross-sectional analytic study was carried out in children in age group 10 to 15 years to assess the prevalence of anxiety symptoms amongst them and their association with parenting style. Results: The study participants (N=499) consisted of 53.31% males and 46.69% females. Children showing anxiety showed a consistently reducing pattern with increase in age till attainment of 15 years of age. High anxiety scores were associated with authoritarian parenting style adopted by father with odds ratio 1.633. Conclusions: The study showed that parenting styles and academic scores are significantly associated with the anxiety symptoms in children of preadolescent age group. Screening children for symptoms of anxiety at an early adolescent stage and counselling of parents for showing responsive parenting behaviour is of paramount importance.